Mechanical Performance of Alkali-Treated Rattan Strips with Epoxy Coating for Sustainable Composite Applications - Sujentheran Nair Kalatharan; Al Ichlas Imran; Agustinus Purna Irawan; Januar Parlaungan Siregar; Tezara Cionita; Deni Fajar Fitriyana; Samsudin Anis; Rozanna Dewi; Yuris Setyoadi; Wisnu Prayogo (Advance Sustainable Science Engineering and Technology, 2025)
The use of natural materials like rattan in eco-friendly composites is gaining attention in materials engineering. However, its hydrophilic nature and interaction with other materials can affect mechanical strength. This study investigates how variations in rattan size and alkali treatment influence the tensile properties of single rattan strips through an epoxy dipping process. Rattan was prepared with varying lengths (5–15 cm), widths (3–8 mm), and a consistent thickness (0.5 mm). Alkali treatment used 5% and 10% NaOH concentrations for 1 and 24 hours. Tensile testing showed that a 5 cm × 8 mm strip achieved the highest tensile strength (49.95 MPa), Young's modulus (3562.77 MPa), and low strain (5.4%), while the 15 cm × 3 mm strip had the lowest strength (9.48 MPa) and modulus (475.69 MPa) with higher strain (10.32%). A 5% NaOH treatment for 24 hours improved adhesion and performance, while 10% caused degradation.